2021
DOI: 10.21203/rs.3.rs-154990/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insisting on Life Dignity: Advance Care Planning in Taiwan During COVID-19 Pandemic

Abstract: Background:The coronavirus disease 2019 (COVID-19) outbreak is a global public health crisis that has affected the implementation of advance care planning (ACP) in Taiwan. The purpose of this study is to (1) confirm that COVID-19 significantly reduced public participation in ACP, (2) identify factors influencing the implementation of ACP during the COVID-19 pandemic and how they differ from those before the COVID-19 outbreak.Methods: An observational study from retrospective review of medical chart and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“… attenuata exhibits clear morphological differentiation. Several authors have recognized all these characters to differentiate species ( Hayata 1912 ; Liu and Ying 1978 ; Yang et al 2001 ; Wang 2004 ; Chao 2016 ; Lu et al 2020 ). A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… attenuata exhibits clear morphological differentiation. Several authors have recognized all these characters to differentiate species ( Hayata 1912 ; Liu and Ying 1978 ; Yang et al 2001 ; Wang 2004 ; Chao 2016 ; Lu et al 2020 ). A.…”
Section: Discussionmentioning
confidence: 99%
“… attenuata (Hayata) Ying. Subsequently, Yang et al (2001) demonstrated that the previously described three species differed from A. elatior , and that A.…”
Section: Introductionmentioning
confidence: 93%